2021
DOI: 10.1039/c9fd00112c
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic carbon nitrides as platforms for single-atom photocatalysis

Abstract: Herein we demonstrate that adding single-atoms of selected transition metals to graphitic carbon nitrides allow the tailoring of their electronic and chemical properties of these 2D nanomaterials, directly impacting their...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“… 47 51 Moreover, PHI-CN materials offer another interesting opportunity in that the alkaline metals could be replaced by other transition metals through cation exchange strategies, thus potentially leading to CN–single atom materials. 52 …”
Section: Two-dimensional Metal-free Photocatalysts: Protagonists Minmentioning
confidence: 99%
“… 47 51 Moreover, PHI-CN materials offer another interesting opportunity in that the alkaline metals could be replaced by other transition metals through cation exchange strategies, thus potentially leading to CN–single atom materials. 52 …”
Section: Two-dimensional Metal-free Photocatalysts: Protagonists Minmentioning
confidence: 99%
“…This enables the comparison of forcefields with higher theory methods such as DFT, which are too costly to be applied even for small clusters. It was also possible to study the interaction of carbon nitride sheets in order to build a multilayer structure and its further interaction with different cations 27 to build a single-cation catalyst using quantum chemistry energies from the GFN1-xTB Hamiltonian. 28 These very successful applications of our method within a quantum chemical potential energy surface might seem enough to prove the effectiveness of our proposal, but we will now present the proof of concept for a more complex application which raises a considerable interest in applied problems ranging from chemistry to biology and materials science: the thermodynamics of interactions involving electronic excited states.…”
Section: Resultsmentioning
confidence: 99%
“…The ion exchange strategy was reported to be another facile wet-chemistry route to fabricate SACs. 126,180,181 Zeng et al demonstrated that Pt SAs with a high loading amount of 8.7 wt% were conned in the interlayer nanospace of g-C 3 N 4 by the ion exchange method (Fig. 6a), showing an enhanced photocatalytic HER performance due to the reduced proton transfer barrier induced by charge polarization effects around Pt SAs.…”
Section: Unique Fabrication Routes Of Sacs For Photocatalytic and Pho...mentioning
confidence: 99%
“…Colombari et al have employed poly(heptazine imides) (PHIs) as 2D substrates to successfully fabricate various SAbased photocatalysts (e.g., Ni, Pt and Ru) by the ion exchange method without introducing other metal ions as exchange sites in the fabrication of SACs based on g-C 3 N 4 -K 126 due to the more coordination possibilities of the heptazine rings in PHIs to anchor metal SAs. 180 In such an ion exchange method, the substrate powders were simply dispersed in the metal solutions (RuCl 3 , NiCl 2 or H 2 PtCl 6 ) to atomically anchor metal species. In another study, Yu et al have employed calcium alginate hydrogel (AG-Ca) as a starting substrate for the loading of Cu SAs by the ion exchange route for the electrocatalytic oxygen reduction reaction (ORR).…”
Section: Unique Fabrication Routes Of Sacs For Photocatalytic and Pho...mentioning
confidence: 99%
See 1 more Smart Citation